(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Ama is a fundamental pathological concept in Ayurveda, described as an improperly digested or unprocessed metabolic by-product formed due to hypofunctioning of Agni. Mandagni leads to the formation of Apakwa Ahara Rasa, which undergoes fermentation and putrefaction, resulting in Ama. Classical Ayurvedic texts describe multiple levels of Agni—Jatharagni, Dhatvagni, and Bhutagni—and impairment at any of these levels contributes to Ama formation. Ama possesses distinct biophysical properties such as heaviness, stickiness, foul smell, and obstructive nature, which enable it to combine with Dosha and Dusya, forming Sama-dosa-dusya complexes. Systemic circulation of Sukshma Ama leads to Srotorodha and Khavaigunya, resulting in various gastrointestinal and systemic disorders, notably Amavata. Clinically, Amavata shows striking similarities with Rheumatoid Arthritis (RA), an autoimmune disorder. The present article reviews the classical concept of Ama, its formation, properties, and systemic effects, and explores its antigenic potential in relation to the pathogenesis of rheumatoid arthritis.